A new target of radiotherapy combined with immunotherapy: regulatory T cells - Song, Dongmei; Ding, Yun (Frontiers in Immunology, 2024)
Radiotherapy is one important treatment for malignant tumours. It is widely believed today that radiotherapy has not only been used as a local tumour treatment method, but also can induce systemic anti-tumour responses by influencing the tumour microenvironment, but its efficacy is limited by the tumour immunosuppression microenvironment. With the advancement of technology, immunotherapy has entered a golden age of rapid development, gradually occupying a place in clinical tumour treatment. Regulatory T cells (Tregs) widely distributing in the tumour microenvironment play an important role in mediating tumour development. This article analyzes immunotherapy, the interaction between Tregs, tumours and radiotherapy. It briefly introduces immunotherapies targeting Tregs, aiming to provide new strategies for radiotherapy combined with Immunotherapy.